Som Tradition for Interreligious Harmony and Natural Preservation - Muhamad Yusuf; Marwan Sileuw; Rachmad Surya Muhandy; Novita Mulyanita (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
The article particularly portrays and studies the Matbat tribe. The Matbat tribe inhabitants establish a system to unite the Matbat people to create stability and peace in overcoming external situations. The intriguing part of the Matbat tribe is that they, starting from an individual level, keep preserving their communal tradition to sustain peace among them and defend their territory. The customary structure of the Matbat people in West Misool was created based on mutual agreement with the roles, duties and functions that are obtained to maintain balance and harmony aimed at kinship values. There are various symbols in the implementation of the Som, which act as a vehicle of conception that has a meaning as mediation that is actualization in daily life. Som's tradition is a unifying tool for the Matbat indigenous people. The procedures for implementing the tradition are determined by customs arranged in the Matbat customary structure. The Som tradition is an annual event held by the villagers and has the power of customary law that regulates the two villages. The Som tradition is carried out from generation to generation. It develops into values firmly held by the indigenous peoples, not only as their perspective on natural resource management policy. It also as the respect of the Younger Brother (Magey village, which is Protestant Christian) to the Elder Brother (Gamta village, which is Muslim), and as a collective awareness composed in creating a moral balance for indigenous peoples to maintain harmony.